Respons Pertumbuhan dan Produksi Bawang Sabrang (Eleutherine americana Merr.) Terhadap Waktu dan Dosis Aplikasi Arang Sekam - Marianus Sitepu; Haryati Haryati; Ferry Ezra Sitepu (Universitas Sumatera Utara, 2015)
Using traditional medicine growing rapidly lately. One of medicinal plant that have been developedis sabrang shallot (Eleutherine americana Merr.) This research aims for getting the best time anddose application of sabrang shallot. The researched was carried out at Field Trials of AgricultureFaculty North Sumatera University ( ± 25 m dpl) on May-October 2014, using a FactorialRandomized Block design with two factors are time aplication (2 weeks before planting, 1 weekbefore planting and when planting) and dose application of husk (1,5; 3; 4,5; 6 kg/plot or 10, 20, 30,40 ton/ha) by three replication. Data were analized with ANNOVA and continued with DuncanMultiple Range Test (DMRT). The parameters observed were age sprouts, plant height, number ofleaves, age flowering , number of tillers, number of bulbs per sample, wet bulbs weight per sample.The results of research shows that time and dose application of husk were significantly differ forplant height, number of leaves and number of sprouts.Key words : Time application, dose of husk , sabrang shallot.